Sleep and Student Success: The Role of Regularity vs. Duration - Phuc Luong; Lester Lusher; Vasil Yasenov (Institute of Labor Economics (IZA), 2017)
Recent correlational studies and media reports have suggested that sleep regularity – the variation in the amount of sleep one gets across days – is a stronger determinant of student success than sleep duration – the total amount of sleep one receives. We identify the causal impacts of sleep regularity and sleep duration on student success by leveraging over 165,000 student-classroom observations from a large university in Vietnam where incoming freshmen were randomly assigned into course schedules. These schedules varied significantly: some had the same daily start time across the week, while others experienced extreme shifts. Across a multitude of specifications and samples, we precisely estimate no discernible differences in achievement between students with highly varying start times versus students with consistent schedules. Moreover, we find much smaller gains to delayed school start times compared to previous studies.
Keywords: I20; I21; I23; 330; school start time; sleep regularity; education policy